1999
DOI: 10.13181/mji.v8i2.693
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study of the two-period of epidemiological analysis of risk factors for breast cancer in Indonesia. Does it change?

Abstract: AbstrakPenelitian kasus kontrol kanker payudara dalam aspek epidemiologi, khuswnya tentang faktor risiko telah dun kali dilakukan di Indonesia. Pertama kali daLam tahun [1980][1981] In the second study, performed under the International Collaborative Study on Breast Cancer betyveen Indonesia and Japan (University of lwlonesiafrom Indonesia and Nagoya University and Cancer Institute Tokyofrom Japan), 300 cases ofbreast cancer were compared to 600 matched controls. [n comparative analysis between the two studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…9 while the mean age of cervical cancer and breast cancer was 54 years and 57 years respectively . According to Ramli,19 the mean age of breast cancer was 46.9 years. The median age of nasopharyngeal carcinoma was 43 years, younger than the study of Sutjipto et al who found 50 years as the median age.…”
Section: Resultsmentioning
confidence: 99%
“…9 while the mean age of cervical cancer and breast cancer was 54 years and 57 years respectively . According to Ramli,19 the mean age of breast cancer was 46.9 years. The median age of nasopharyngeal carcinoma was 43 years, younger than the study of Sutjipto et al who found 50 years as the median age.…”
Section: Resultsmentioning
confidence: 99%